2015
DOI: 10.1039/c4sc02379j
|View full text |Cite
|
Sign up to set email alerts
|

Harnessing selenocysteine reactivity for oxidative protein folding

Abstract: Turbo-charged folding with selenium: targeted replacement of cysteines in proteins with selenocysteines is a valuable strategy for increasing the rates of oxidative protein folding, altering folding mechanisms, and rescuing kinetically trapped intermediates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
64
0
4

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 66 publications
(71 citation statements)
references
References 36 publications
3
64
0
4
Order By: Relevance
“…Combined with mechanistic insights, these results suggested that COCs could cross the lipid bilayer membrane as molecular walkers through successive thiol–dichalcogenide exchange reactions along disulfide tracks in membrane proteins (Figure A) after reacting with proximal exofacial thiols (Figure B) . Such processes could cause temporary local protein denaturation and transient micellar defects in the membrane to allow the passage of large substrates. The transferrin receptor mentioned above is a possible candidate of a disulfide track, having intermolecular disulfide bridges at the entry into the membrane (C89, C98) and nearby thiols, although possibly acylated (C62, C67) .…”
Section: Figurementioning
confidence: 94%
“…Combined with mechanistic insights, these results suggested that COCs could cross the lipid bilayer membrane as molecular walkers through successive thiol–dichalcogenide exchange reactions along disulfide tracks in membrane proteins (Figure A) after reacting with proximal exofacial thiols (Figure B) . Such processes could cause temporary local protein denaturation and transient micellar defects in the membrane to allow the passage of large substrates. The transferrin receptor mentioned above is a possible candidate of a disulfide track, having intermolecular disulfide bridges at the entry into the membrane (C89, C98) and nearby thiols, although possibly acylated (C62, C67) .…”
Section: Figurementioning
confidence: 94%
“…Furthermore, because diselenide bonds are more stable than disulfides (relative to their respective reduced forms), substituting Sec residues in strategic positions can improve folding efficiency even via non‐native pairing followed by protein structure‐driven rearrangement . This counterintuitive outcome was demonstrated in the case of the bovine pancreatic trypsin inhibitor (BPTI), a classical model of protein folding: pairwise replacement of Cys5 and Cys14 with Sec yielded a non‐native diselenide bond that was associated with enhanced folding efficiency because trapped intermediates that otherwise confound the folding of WT‐BPTI were sidestepped …”
Section: Introductionmentioning
confidence: 99%
“…The oxidative folding of reduced wild type (WT)‐BPTI and MT‐BPTI was studied in parallel under various conditions. We first tested under standard conditions, wherein the reduced WT‐BPTI folded to form two one‐disulfide intermediates [30–51] and [5–55]. As the reaction proceeded, the two‐disulfide intermediates N′ and N* start to appear; these intermediates are stable over time because of their quasi‐native structures .…”
Section: The Case Of Bptimentioning
confidence: 99%